Impact of fipronil on the mushroom bodies of the stingless bee Scaptotrigona postica - Jacob, Cynthia R. O. [UNESP]; Soares, Hellen M. [UNESP]; Nocelli, Roberta C. F.; Malaspina, Osmar [UNESP] (Wiley-Blackwell, 2015)
BACKGROUND: Studies on stingless bees are scarce, and little is known about these insects, especially regarding the effects of contamination by neurotoxic insecticides, which can cause damage to important structures of the insect brain. This study evaluated the morphological changes in the intrinsic neurons of the protocerebral mushroom bodies (Kenyon cells) of the stingless bee Scaptotrigona postica after exposure to different doses of fipronil, using light microscopy and transmission electron microscopy. This region of the brain was selected for analysis because of its importance as a sensory integration centre.RESULTS: In both oral and topical treatments, Kenyon cells presented pyknotic profiles, suggesting cell death. Statistical analysis showed significant differences among doses and exposure times. Transmission electron microscopy revealed changes in the nucleus and cellular organelles. Depending on the dose, the characteristics observed suggested apoptotosis or necrosis.CONCLUSION: This study demonstrates the toxic effects of fipronil. An increase in the number of pyknotic profiles of Kenyon cells of mushroom bodies was observed even at the sublethal doses of 0.27 ng AI bee(-1) and 0.24 ng AI mu L-1 in the topical and oral treatments respectively. Also, differences in the number of pyknotic profiles were dose and time dependent. (C) 2014 Society of Chemical Industry
Keywords: apoptosis; cytotoxicity; phenylpyrazole; necrosis; nervous system